2005
DOI: 10.1183/09031936.05.00061405
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Aspergillus fumigatus challenge on exhaled and nasal NO levels

Abstract: Several studies have previously shown that exposure to indoor air microbes from moisture-damaged buildings can cause adverse health effects. Aspergillus fumigatus is one of the best-documented moulds causing health problems to those exposed.In this study, inhalation of a commercial A. fumigatus solution was assessed, to establish if it would have effects on fractional exhaled (FeNO) and nasal (FnNO) nitric oxide levels and on lung function. The results were compared with placebo challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
11
1
Order By: Relevance
“…However, available data on expression dynamics of some biomarkers were limited or inconsistent. For example, an increase in FeNO has been observed right after swimming (Carbonnelle et al 2002) and also 6 hr after mold exposure (Stark et al 2005). Therefore, undetected changes in some biomarkers due to inappropriate sample timing cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, available data on expression dynamics of some biomarkers were limited or inconsistent. For example, an increase in FeNO has been observed right after swimming (Carbonnelle et al 2002) and also 6 hr after mold exposure (Stark et al 2005). Therefore, undetected changes in some biomarkers due to inappropriate sample timing cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…A change in the concentration of lung surfactant proteins in serum has been proposed as a marker to detect early permeability changes in the lung epithelium (Broeckaert et al 2000). Fractional concentrations of orally exhaled nitric oxide (FeNO) is a marker of eosinophilic airway inflammation (Choi et al 2006) and has been shown to increase after short-term exposure to mold (Stark et al 2005). Soluble molecules can be detected in EBC, including proinflammatory cytokines, growth factors, and oxidative stress biomarkers, and have been used to monitor different aspects of diseases such as asthma or chronic obstructive pulmonary disease, as well as the effects of environmental stressors or physical exercise (Bonsignore et al 2003; Carbonnelle et al 2002, 2008; Massin et al 1998; Nanson et al 2001).…”
mentioning
confidence: 99%
“…So far, several studies have shown an elevation of FENO after bronchial allergen challenges (17–19). However, to our knowledge, only one study exists, which has shown a rise of FENO after nasal allergen challenge in children with allergic rhinitis to mites (20), while other authors could not provoke an elevation of FENO in patients with rhinitis (21, 22).…”
mentioning
confidence: 99%
“…However, there are inconsistent findings among the few studies that have explored the association between eNO levels and indoor microbial contamination. Experimental studies with adults have demonstrated elevated eNO levels after respiratory challenge with endotoxin (Kitz et al, 2006) and Aspergillus fumigatus (Stark et al, 2005). In contrast, Purokivi et al (2002) measured eNO levels in employees working in moisture damaged buildings versus reference buildings and detected no association.…”
Section: Introductionmentioning
confidence: 99%